Negotiating the disabled body: representations of disability in early Christian texts - Solevåg, Anna Rebecca (Early Christianity and its literature, 2018)
Cover; Contents; Acknowledgments; Abbreviations; Introduction; Healings as Narrative Prosthesis in Mark; John and the Symbolic Significance of Disability; Disabling Women in the Acts of Peter; The Rhetoric of Madness and Demon Possession; Judas the Monster; Eunuchs in/and the Kingdom of God; Conclusion; Bibliography; Ancient Sources Index; Modern Authors Index.